The Effects of Polyphenol Supplementation in Addition to Calorie Restricted Diets and/or Physical Activity on Body Composition Parameters: A Systematic Review of Randomized Trials - Llaha, Fjorida; Zamora-Ros, Raul (Frontiers in Nutrition, 2020)
Background: Both, calorie restricted diets (CRD) and physical activity (PA) are conventional obesity therapies but their effectiveness is usually limited in the long-term. Polyphenols are bioactive compounds that have shown to possess some anti-obesity properties. The synergic effects between dietary polyphenols and CRD or PA on body weight and fat are supported by several animal studies, but evidence in human is still inconsistent. Thus, our aim was to review the combined effects of polyphenol supplementation with CRD and/or PA on body weight and fat, body mass index (BMI) and waist circumference (WC) in overweight or obese adults. Methods: Electronic databases (PubMed, Web of Science and Cochrane CENTRAL) were searched for randomized clinical trials (RCT) examining the combination of polyphenols with CRD and/or PA (up to December 31st, 2019). Articles were included if they had a duration of intervention ≥ 4 weeks. Both, quality and risk of bias of the included studies were assessed using the Cochrane RoB2 Tool. Results: The review included 4 and 11 RCTs investigating the anti-obesity effects of polyphenol supplementation combined with CRD and PA, respectively. Isoflavone supplementation may increase fat loss during exercise among post-menopausal women in non-Asian studies. In the rest of RCTs regarding polyphenol supplementation and CRD or PA, no additive changes were found. Conclusion: The results do not yet support polyphenol supplementation as a complementary strategy for enhancing the effectiveness of CRD and PA on weight and fat loss. However, this review suggests that isoflavone and soy products combined with lifestyle changes, especially exercise, provide additional beneficial anti-obesity effects in postmenopausal women. The potential role of polyphenols alone or, especially, in addition to conventional therapies (CRD and PA) mostly remains uncertain; and therefore, larger and longer RCTs examining these effects are needed.